Genomic Characterization of Listeria monocytogenes Isolated From Ready-to-Eat Meat and Meat Processing Environments in Poland - Kurpas, Monika (Front Microbiol, 2020)
Listeria monocytogenes is one of the major foodborne pathogens. Isolates of PCR-serogroups IIb (n = 17) and IVb (n = 31) recovered from food (n = 33) and food processing environment (n = 15) in Poland were characterized using whole genome sequencing. Most isolates belonged to Multi-Locus Sequence Type (MLST) ST2 (31.3%) and ST5 (22.9%). Core genome MLST (cgMLST) analysis classified isolates into seven sublineages (SL) and 25 different cgMLST types (CT). Consistent with the MLST results, most sublineages were SL2 and SL5. Eleven isolates harbored aacA4 encoding resistance to aminoglycosides, three isolates harbored emrC (n = 3) and one brcABC (n = 1) encoding tolerance to benzalkonium chloride. Isolates belonging to SL5 CT2323 carried a so far unreported inlB allele with a deletion of 141 nucleotides encoding the β-repeat sheet and partially the GW1 domain of InlB. Comparison with publicly available genome sequences from L. monocytogenes isolated from human listeriosis cases in Poland from 2004 to 2013 revealed five common CTs, suggesting a possible epidemiological link with these strains. The present study contributes to characterize the diversity of L. monocytogenes in ready-to-eat (RTE) meat and meat processing environments in Poland and unravels previously unnoticed links with clinical cases in Europe.